Screening investigation of patients with diffuse liver diseases - I. Yu. Pirogova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To present data on screening investigation of patients at suspicion for diffuse liver disease, including series of routine methods specified by medical standards.Original positions. Article presents data on diagnostic accuracy, sensitivity, specificity of taken into account methods both separately and at integrated application in comparison to subsequent biopsy and liver elastometry.